Efficacy of a Modulated Viscosity-dependent Temperature/nanoparticles Concentration Parameter on a ‎Nonlinear Radiative Electromagneto-nanofluid Flow along an Elongated Stretching Sheet - Ji-Huan He; Nasser S. Elgazery; Khaled Elagamy; Nader Y. Abd Elazem (Journal of applied and computational mechanics, 2023)
The purpose of the present communication is to investigate the flow of a radiative electromagnetic-Casson nanofluid past a stretching sheet under the impacts of a chemical reaction and nonlinear thermal radiation. To enrich the blood flow, a modulated viscosity/thermal conductivity dependent temperature/nanoparticles concentration parameter is included in the governing equations. The system of PDEs is transformed to ODEs by invoking similarity transformations and then solved numerically by the well- known fourth-order Runge-Kutta integration scheme based on shooting approach. The main factors affecting the Casson fluid’s temperature profiles are revealed.